Čerenkov radiation in vacuum from a superluminal grating - Daigo Oue; Kun Ding; J. B. Pendry (Physical Review Research, 2022)
Nothing can physically travel faster than light in vacuum. There are several ways proposed to bypass the light barrier and produce Čerenkov radiation (ČR) in vacuum. In this paper, we theoretically predict ČR in vacuum from a spatiotemporally modulated boundary. We consider the modulation of traveling wave type and apply a uniform electrostatic field on the boundary to generate electric dipoles. Since the induced dipoles stick to the interface, they travel at the modulation speed. When the grating travels faster than light, it emits ČR. In order to quantitatively examine this argument, we need to calculate the field scattered at the boundary. We utilize a dynamical differential method, which we developed in a previous paper, to quantitatively evaluate the field distribution in such a situation. We can confirm that all scattered fields are evanescent if the modulation speed is slower than light while some become propagating if the modulation is faster than light.